Missed Massive Morel-Lavallee Lesion - Shunsuke Takahara; Keisuke Oe; Hironori Fujita; Atsushi Sakurai; Takashi Iwakura; Sang Yang Lee; Takahiro Niikura; Ryosuke Kuroda; Masahiro Kurosaka (Case Reports in Orthopedics)
A Morel-Lavallee lesion (MLL) involves posttraumatic fluid collection around the greater trochanter. Many cases of MLL are missed at the initial evaluation, and the treatment of MLL is not well established. We present two cases in which MLL was missed at the initial evaluation. Case 1. A 65-year-old man was run over by a parade float. There was subcutaneous hematoma around the left greater trochanter, and no fracture was found. We diagnosed this injury as MLL on the 7th day after the trauma. Although we performed percutaneous drainage, the injured area was infected. Case 2. A 57-year-old man was hit by a train in a factory. There was an iliac wing fracture, but an MLL was not initially recognized. On the 6th day after the trauma, when performing open reduction and internal fixation for the iliac fracture, we recognized the lesion and performed percutaneous drainage simultaneously. This lesion also became infected. In these two cases, the wounds finally healed after a long duration of treatment. We suggest that it is important to keep this injury in mind and debride the lesion early and completely in the treatment course.